Análise de evasão no ensino superior: uma proposta de diagnóstico para o Campus de Laranjeiras - Feitosa, Jamille Muniz (2016)
With the expansion of the vacancies in the brazilian public higher education, dropout has also increased, which infers a problem to be handled carefully by the management of higher education. This work has as main objective to make a diagnosis about evasion in undergraduate courses Campus Laranjeiras, the Federal University of Sergipe (UFS), in order to point out the influence of variables related to internal and external factors of the institution, as well as factors relating to the individual characteristics of the student to the occurrence of the event. It was used as data collection instrument a questionnaire to dropout students calculated the frequency and performed descriptive analysis. The results showed the profile of dropouts, mostly as female, with an average of thirty, brown color, family income between 1 to 3 minimum wages, no bondholder and newly entering students. The campus had an average of 16.8% of evasion in the period from 2010 to 2014, and the most relevant reasons, according to the result of the survey of perception with the students, corresponded, firstly, to the location of the campus versus housing transportation , followed by the hours of the courses offered, the conciliation with work and the demotivation with the course.